Asymmetric Airy pulse inversion in a semiconductor optical amplifier under third-order dispersion - Lucien Mandeng Mandeng; Souang Kemedane Boukar; Clément Tchawoua (AIP Advances)
In this work, we report the asymmetric Airy pulse inversion (AAPI) phenomenon under third-order dispersion (TOD) in a semiconductor optical amplifier (SOA) waveguide, including the dispersion and saturation gains in addition to the internal linear losses as well as the two-photon absorption (TPA). A model of the studied system is conducted, leading to the nonlinear Schrödinger equation, which includes all the aforementioned parameters. In the linear regime, we analytically formulate the envelope vs the propagation distance in agreement with the numerical simulation. Then, we obtain the AAPI phenomenon numerically and show that the inverted output signal is amplified under the SOA dispersion gain interacting with the TOD. However, the internal linear losses being deleterious to this amplification surprisingly allow the phenomenon to appear earlier by increasing the linewidth enhancement. In the nonlinear regime, the saturation gain is found to be beneficial without major contribution from the TPA.